ChemInform Abstract: Environmentally Benign Deprotection of Dithioacetals Using 30% Hydrogen Peroxide Catalyzed by Fe(acac)3 and Sodium Iodide. Issue 3 (21st January 2014) - Kirihara, Masayuki; Suzuki, Satoshi; Ishizuka, Yuki; Yamazaki, Kento; Matsushima, Ryoji; Suzuki, Takaya; Iwai, Toshiaki
Abstract The reaction of dithioacetals with excess aqueous hydrogen peroxide in the presence of catalytic amounts of iron(III) acetylacetonate and sodium iodide efficiently produces the corresponding carbonyl compounds in high yields.